2017
DOI: 10.1017/jfm.2017.822
|View full text |Cite
|
Sign up to set email alerts
|

Turbulence, entrainment and low-order description of a transitional variable-density jet

Abstract: Geophysical flows occur over a large range of scales, with Reynolds numbers and Richardson numbers varying over several orders of magnitude. For this study, jets of different densities were ejected vertically into a large ambient region, considering conditions relevant to some geophysical phenomena. Using particle image velocimetry, the velocity fields were measured for three different gases exhausting into air – specifically helium, air and argon. Measurements focused on both the jet core and the entrained am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
14
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 61 publications
7
14
0
Order By: Relevance
“…This can be related to findings by Ricou and Spalding who reported that entrainment rate in near exit positions was higher for Re <10 4 . Likewise, Viggiano et al found that turbulent jets at lower Reynold numbers exhibit higher entrainment and velocity fluctuations than experienced at Re >8000 due to smaller eddies that develop along with the shear layer.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…This can be related to findings by Ricou and Spalding who reported that entrainment rate in near exit positions was higher for Re <10 4 . Likewise, Viggiano et al found that turbulent jets at lower Reynold numbers exhibit higher entrainment and velocity fluctuations than experienced at Re >8000 due to smaller eddies that develop along with the shear layer.…”
Section: Resultsmentioning
confidence: 96%
“…The common method of determining entrainment flow is applying the integral solution (Equation 1) of streamwise velocity profiles at various downstream distances . The entrainment flow rate ( Q e ) up to a point x downstream can be determined by the relationship.Qe=QxQ0…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Year Frequency Jet Type Study Type (Hz) Kercher et al [6] 2003 1-1000 synthetic Travnicek and Tesar [8] 2003 106-692 synthetic smoke Smith and Swift [1] 2003 synthetic and Schlieren continuous Pavlova et al [9] 2006 420-1200 synthetic Arik [10] 2008 4500 synthetic Chaudhari et al [11] 2009 100-350 synthetic Bazdidi-Tehrani et al [12] 2011 16-400 synthetic Biden et al [13] 2012 unforced jet POD in crossflow Biden et al [14] 2012 forced jet POD in crossflow Ghaffari et al [15] 2016 20,000 ultrasonic microblower Ghadi et al [16] 2016 pulsed smoke impinging jet Albright and Solovitz [17] 2016 variable-diameter synthetic jet Firdaus et al [18] 2018 300-700 synthetic Solovitz et al [19] 2018 350-2000 synthetic PIV Viggiano et al [20] 2018 variable-density POD and PIV jet Kristo et al [21] 2021 crossflow jets POD and PIV Present work 2021 20-100 synthetic POD, smoke, Schlieren Pavlova et al [9] found that high-frequency jets removed heat more effectively, but that lower-frequency jets were better for larger separation distances. Many authors found that the optimal frequency for heat transfer was the resonance frequency for the device or the diaphragm [11,18,19].…”
Section: Citationmentioning
confidence: 99%
“…Conditional sampling technique has been applied to particle image velocimetry (PIV) data for a number of different applications. Examples include the spatial mapping of flow events in conjunction with proper orthogonal decomposition [6,7], the study of similarity of Reynolds stress profiles in turbulent boundary layers over rough walls [8][9][10], Blowing-snow transport [11], air-sea interaction aerodynamics [12], and characterization of flow over plant canopies by means of quadrant hole analysis [13]. Longo and Losada [14] used quadrant analysis on PIV data to study the structure of the boundary layer at the air-water interface of wind induced water waves.…”
Section: Introductionmentioning
confidence: 99%